Undifferentiated Pancreatic Carcinoma With Osteoclast-Like Giant Cells: What Do We Know So Far? - Demetter, Pieter; Maréchal, Raphaël; Puleo, Francesco; Delhaye, Myriam; Debroux, Sébastien; Charara, Fadi; Gomez Galdon, Maria; Van Laethem, Jean-Luc; Verset, Laurine (Frontiers in Oncology, 2021)
Undifferentiated carcinoma of the pancreas is a rare and aggressive tumor for which a variety of other terms has been used to describe its histological appearance. In addition, as osteoclast-like giant cells may accompany undifferentiated carcinoma of the pancreas, the WHO Classification separates undifferentiated carcinoma with osteoclast-like giant cells (UC-OGC) from plain undifferentiated carcinoma, implying there are a few clinical and histopathological differences. UC-OGC was initially thought to show worse prognosis than that of invasive ductal adenocarcinoma of the pancreas, because it is frequently found to be unresectable at diagnosis due to advanced stages and tends to recur early even after complete surgical resection. When true UC-OGGs are carefully dissected out from other anaplastic carcinomas, it becomes, however, clear that UC-OGCs do have more indolent behavior, especially the pure UC-OGCs. This mini-review summarizes the current knowledge on UC-OGC.